EXEGESIS IN CREATIVE ARTS THESIS - Su-hie Ting; Saiful Bahari Mohd Yusoff; Nancy Kissam; Wan Jamarul Imran Wan Abdullah Thani; Noorhaslina Senin (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
Writing creative arts theses based on a social sciences model does not allow documentation of the creative process. The study examined content structuring of creative arts theses. The specific objectives were to examine creative arts lecturersâ€™ views on studentsâ€™ problems in thesis writing, analyse the content structuring of creative arts theses, and formulate a conceptual model of the content structure of the exegesis to accompany creative work. The study involved analysis of theses writing guidelines and the content of research methodology courses in two Malaysian universities offering creative arts academic programmes. The results showed recommendations on the conventional social science thesis structure with some space for the design processes. In addition, the analysis of 11 creative arts theses revealed confusion on the content structuring and student weaknesses in amassing research findings to contextualise the creative work. Based on the results, a conceptul model of creative arts exegesis with separate chapters for â€œProposed final product and human factor issuesâ€ and â€œintellectual property documentationâ€ was formulated and validated by creative arts lecturers. The exegesis model which builds in design processes and research processes would resolve issues on unclear expectations in creative arts students theses and elevate the significance of the creative work.